The traveling deliveryman problem under uncertainty: Fundamentals for flexible supply chains. (April 2022) - Di Pretoro, Alessandro; Negny, Stéphane; Montastruc, Ludovic
Highlights: A procedure for supply chain flexibility assessment is presented. The new procedure can be scaled up to more complex systems. Indicators used for unit operations are adapted to operational research. Identifying critical parameters allow to have reliable cost expectations. Abstract: In recent years, supply chain optimization has become a major topic in operational research. Huge efforts were made to outline effective methodologies both from computational and final solution quality perspective. However, besides being optimal, one major need of supply chains is flexibility and adaptability to disturbances. This research work aims at the definition of a thorough procedure for flexible supply chain design able to exploit deterministic and stochastic flexibility indices. The Traveling Deliveryman Problem was then selected as case study since it represents the most basic operational research problem. The adaptation of flexibility assessment methodologies, primarily conceived for unit operations, provides good results and allows to properly identify criticalities. In addition, it proves that the optimal solutions under uncertainty are confined to a limited subset among million possible alternatives according to the expected deviation nature. This procedure is then worth to be extended to more complex systems in future studies.